Selection of build orientation for optimal support structures and minimum part errors in additive manufacturing. (10th November 2017) - Das, Paramita; Mhapsekar, Kunal; Chowdhury, Sushmit; Samant, Rutuja; Anand, Sam
ABSTRACT: Additive Manufacturing (AM) incorporates a group of processes which utilize a layer-based material deposition approach to manufacture parts. These processes are now widely used in the industry as the primary manufacturing process for fabricating high precision parts. The dimensional accuracy of the parts and components manufactured using AM depend mainly on the type of Additive process used and the process parameters. The part build orientation is one of the principal process parameters which has a direct influence on the staircase effect and volume of support structure required for building the part. These factors eventually contribute to the surface finish, dimensional accuracy, and the post-processing requirements. In this paper, an optimization model is developed to obtain the build orientation which will minimize the support structure volume as well as support contact area and maximize the support structure removal while satisfying all the GD&T callouts. The mathematical correlation of cylindricity, flatness, parallelism, and perpendicularity tolerances with build orientation is analyzed and developed. A voxel-based approach is employed to calculate support structure requirement at any part build orientation, while a ray tracing approach is used to calculate the accessibility of supports and identifying removable supports. GRAPHICAL ABSTRACT: